Trends and trajectories in employee green behavior research - Ali, Azlan; Juan, Huang (Frontiers in Sociology, 2024)
With environmental protection awareness increasing, green innovation has become a key way for enterprises to achieve sustainable development. Research trends on employee green behavior are an important basis for formulating green behavior incentive measures and a key foundation for further exploring green innovation. However, due to the large amount of literature on employee green behavior, obtaining research trends directly related to employee green behavior takes time and effort. To solve this problem, this paper takes the relevant published literature on research on employee green behavior from 2009 to 2024 as the research object. It uses CiteSpace software to study the research trends of employee green behavior from the number change analysis of published literature, distribution region analysis of published literature, influence analysis of main authors of published literature, keyword analysis, and high-frequency word analysis. The research results show that the publication of literature on employee green behavior has been steadily increasing since 2018, and the relevant research mainly focuses on the impact of green behavior motivations, green behavior emotional factors, green behavior performance results, green self-energy efficiency, and other aspects on employee green behavior. Based on the research results, further summaries and suggestions are given to provide references for the subsequent related research in this paper.